PENGARUH METODE PEMBELAJARAN SYNERGETIC TEACHING TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI IPA SMA NEGERI 9 MERANGIN - Fitri Handayani; Ririn Dewi Anggraini (Fokus | Jurnal Pendidikan STKIP YPM Bangko, 2022)
The research uses the synergetic teaching learning method. The type of research used is experimental quantitative by connecting two variables, namely the synergetic teaching learning method as the independent variable and the learning outcomes of biology as the dependent variable. The population of this study were all students of class XI IPA SMA Negeri 9 Merangin as many as two classes consisting of 42 students. The sampling technique used is Simple Random Sampling. The sample selected was class XI A as the experimental class and class XI B as the control class. Data were collected using a test technique in the form of an essay test on the structure of various tissues found in plants. The results of the analysis of the final test data obtained an average of 60,681 in the experimental class, variance 77322,925 and standard deviation 278.07, while the control class obtained data of 53.9, variance 55198,683, and standard deviation 234,944. The analysis technique used t-test. The results of hypothesis testing are obtained tcount = 3.760 and ttable = 1.684. Because tcount > ttable , Ho rejected and H1 accepted. This means that the biology learning outcomes of students using the synergetic teaching learning method are better than the students' biology learning outcomes using the conventional model of class XI science students at SMA Negeri 9 Merangin